Paul Laurence Dunbar : The Life and Times of a Caged Bird - Jarrett, Gene Andrew, 1975- (Book collections on Project MUSE., 2022)
"This biography explores the life of Paul Laurence Dunbar (1872-1906), a major nineteenth-century American poet and one of the first African American writers to garner international attention and praise in the wake of emancipation. While Dunbar is perhaps best known for poems such as "Sympathy" (a poem that ends "I know why the caged bird sings!") and "We Wear the Mask," he wrote prolifically in many genres, including a newspaper he produced with his friends Orville and Wilbur Wright in their hometown of Dayton, Ohio. Before his early death he published fourteen books of poetry, four collections of short stories, and four novels, and also collaborated on theatrical productions, including the first musical with a full African American cast to appear on Broadway. In this book, Gene Jarrett traces Dunbar's personal and professional life in the context of the historical currents that shaped the author's development-to tell, in Jarrett's words, "the full story of an African American who privately wrestled with the constraints of America in the Gilded Age, but who also sought to express or mitigate this strife through the written and spoken word." Jarrett sketches the life and times of Paul Laurence Dunbar in three main parts. Against the backdrop of the Civil War, Reconstruction, and the rise of Jim Crow segregation, the first section, "Broken Home," begins with the lives of Joshua and Matilda, Paul's parents, who were born enslaved, and ends with the years leading up to 1893, when Dunbar published his first book, Oak and Ivy, and befriended Frederick Douglass. The second section, "A True Singer," bookends the era when Paul entered his literary prime and became one of the first professional African American writers. The final section, "The Downward Way," details his troubled marriage to Alice Dunbar-Nelson, his illnesses, including tuberculosis and alcoholism, and his death. An epilogue comments on Dunbar's enduring legacy. The book includes more than 40 black-and-white photographs of Dunbar's family, friends, colleagues, and published works"--